Comments on two-loop Kac-Moody algebras - Ferreira, L. A. [UNESP]; Gomes, J. F. [UNESP]; Zimerman, A. H. [UNESP]; Schwimmer, A. (Elsevier B.V., 1992)
It is shown that the two-loop Kac-Moody algebra is equivalent to a two-variable-loop algebra and a decoupled β-γ system. Similarly WZNW and CSW models having as algebraic structure the Kac-Moody algebra are equivalent to an infinity of versions of the corresponding ordinary models and decoupled abelian fields.